2006
DOI: 10.1177/0038038506063669
|View full text |Cite
|
Sign up to set email alerts
|

Moral Economy and Cultural Work

Abstract: While the ‘culturalization’ of the economy has led some to welcome the ‘turn to life’ (Heelas, 2002) and anticipate the remoralization of economic activity, others argue the cultural turn is conducive only to consolidating neo-liberalism's characteristic demoralization of economic relations.The cultural industries, as a leading sector of the culturalized economy, are seen to be particularly culpable in this respect, offering the illusion of freedom, but actually eroding the ethical basis of work through tenden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(98 citation statements)
references
References 25 publications
2
94
0
2
Order By: Relevance
“…We have shown that, in Germany, the entrepreneur is contrasted unfavourably with more 'serious' ideas of conventional employment in established industry. The resulting outsider image portrays the entrepreneur less as a leader showing others the way (Banks, 2006;Sørenson, 2008) and more as a tolerated inefficiency in the fringes of the economic system, providing some explanation to Germany's low rate of entrepreneurial activity in spite of favourable economic circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that, in Germany, the entrepreneur is contrasted unfavourably with more 'serious' ideas of conventional employment in established industry. The resulting outsider image portrays the entrepreneur less as a leader showing others the way (Banks, 2006;Sørenson, 2008) and more as a tolerated inefficiency in the fringes of the economic system, providing some explanation to Germany's low rate of entrepreneurial activity in spite of favourable economic circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a review of the research on the CCIs, reveals many studies which analyse, for example, the cultural and creative production system Pratt 2004;Adkins, Foth et al 2007;Pratt 2008;Bakhshi and McVittie 2009;Abadie, Friedewald et al 2010;Potts and Cunningham 2010, Taylor 2011), the role played by networks and informal relations (Banks, Lovatt et al 2000;Delmestri, Montanari et al 2005;Adkins, Foth et al 2007;Antcliff, Saundry et al 2007;Dahlstrom and Hermelin 2007;Potts, Cunningham et al 2008;Currid and Williams 2010;Lange 2010;Lingo and O'Mahony 2010), the importance of places and clusters Drake 2003;Mommaas 2004;Neff 2005;Bathelt and Graf 2008;Gwee 2009;Pratt 2009;Collis, Felton et al 2010;Thomas, Hawkins et al 2010) and the conditions and drivers of creative labour (Banks 2006;Comunian 2009). The role of HE institutions within this new CCI landscape in the UK has received some attention (Crossick 2006;Powell 2007;Taylor 2007;Comunian and Faggian 2011) but little with an explicitly regional and urban development focus.…”
Section: Introductionmentioning
confidence: 99%
“…Moral sermaye büyük ölçüde ekonomik yapıyı etkilemektedir. Moral sermaye ve ekonomik yapı arasındaki ilişkiyi Banks (2006), moral ekonomi kavramıyla açıklamaktadır. Banks'a göre ekonomik etkinlikler, moral değer ve normlar çerçevesinde yönlendirilmektedir.…”
Section: Moral Sermayeye Yatırım Yapmakunclassified